The art of meditation and the French Renaissance love lyric : the poetics of introspection in Maurice Scève's Délie, object de plus haulte vertu (1544) - Giordano, Michael (University of Toronto Press, 2010)
"The Art of Meditation and the French Renaissance Love Lyric examines the poetics of meditation in the French love lyric at the height of the Lyonnais Renaissance as illustrated by one of the country's most prominent writers. Maurice Scève's Délie is the first French sequence of poems devoted to a single woman in the manner of Petrarch's Rime. It is also the first Renaissance work to use emblems in a sustained work on love.